Concomitant Carboxylate and Oxalate Formation From the Activation of CO2 by a Thorium(III) Complex. Issue 50 (27th October 2016) - Formanuik, Alasdair; Ortu, Fabrizio; Inman, Christopher J.; Kerridge, Andrew; Castro, Ludovic; Maron, Laurent; Mills, David P.
Abstract: Improving our comprehension of diverse CO2 activation pathways is of vital importance for the widespread future utilization of this abundant greenhouse gas. CO2 activation by uranium(III) complexes is now relatively well understood, with oxo/carbonate formation predominating as CO2 is readily reduced to CO, but isolated thorium(III) CO2 activation is unprecedented. We show that the thorium(III) complex, [Th(Cp′′)3 ] (1, Cp′′={C5 H3 (SiMe3 )2 ‐1, 3}), reacts with CO2 to give the mixed oxalate‐carboxylate thorium(IV) complex [{Th(Cp′′)2 [κ 2 ‐O2 C{C5 H3 ‐3, 3′‐(SiMe3 )2 }]}2 (μ‐κ 2 :κ 2 ‐C2 O4 )] (3 ). The concomitant formation of oxalate and carboxylate is unique for CO2 activation, as in previous examples either reduction or insertion is favored to yield a single product. Therefore, thorium(III) CO2 activation can differ from better understood uranium(III) chemistry. Abstract : A winning combination : The thorium(III) complex [Th{C5 H3 (SiMe3 )2 ‐1, 3}3 ] reacts with CO2 to give a mixed carboxylate–oxalate product (see figure). This reactivity contrasts with better understood uranium(III) CO2 activation, which typically gives oxo and carbonate products via the elimination of CO.